The role of mycotoxin contamination in nutrition: The aflatoxin story - Ayalew, Amare; Hoffmann, Vivian; Lindahl, Johanna; Ezekiel, Chibundu N. (International Food Policy Research Institute, 2016)
Over the past decade, there has been increasing recognition that the quantity of food alone guarantees neither food security nor adequate nutrition as measured by metrics such as hunger, malnutrition, and stunting. Increasingly, policy and decision makers understand the need to include nutritional aspects into improvements of food systems. However, not as fully recognized is that unsafe, contaminated foods thwart these efforts and maintain an unacceptable status quo in food insecurity, poverty, and a range of health-related problems. All of this makes sustainable development more challenging. In 2010, foodborne hazards caused 600 million illnesses and 420,000 deaths across the world, with 40 percent of this disease burden occurring among children under five years of age (Global Panel on Agriculture and Food Systems for Nutrition 2016). Yet food safety has become an important precondition for access to global food markets and, increasingly, for high-value domestic markets in developing countries.